"Doing authentic research" with artifacts to facilitate teacher learning across multiple communities. (September 2021) - Zheng, Xin; Yin, Hongbiao; Wang, Xiaofang
Abstract: The current study reports the learning process of a group of teachers as they move across the school context and a research-oriented professional learning community (PLC). Using the framework of cultural-historical activity theory, this study analyzes the contradictions that teachers encounter among different activity systems and how these contradictions are resolved. The findings show that teachers are engaged in various research activities around "authentic" problems. Mediating tools are deliberately designed and used to address these problems, which facilitate teachers' learning process and the transformation of the community culture. The role of structural design and teacher leadership for teacher learning in PLCs is discussed. Highlights: The processes of teachers' learning and cultural transformation in professional learning communities (PLCs) are analyzed. The "what" and "how" artifacts are deliberately designed to resolve multiple contradictions. The structural design and cultural formation matter for PLC development. Teacher leadership plays a key role in PLC structuring and reculturing.